Cocaine profiling method retrospectively developed with nontargeted discovery of markers using liquid chromatography with time‐of‐flight mass spectrometry data. Issue 3 (27th July 2021) - Carby‐Robinson, Daniel; Dalsgaard, Petur Weihe; Mollerup, Christian Brinch; Linnet, Kristian; Rasmussen, Brian Schou
Abstract: Illicit drug profiling performed by forensic laboratories assists law enforcement agencies through providing information about chemical and/or physical characteristics of seized specimens. In this article, a model was developed for the comparison of seized cocaine based on retrospective analysis of data generated from ultrahigh performance liquid chromatography with time‐of‐flight mass spectrometry (UHPLC‐TOF‐MS) comprehensive drug screening. A nontargeted approach to discover target compounds was employed, which generated 53 potential markers using data from cocaine positive samples. Twelve marker compounds were selected for the development of the final profiling model. The selection included a mixture of commonly used cocaine profiling targets and other cocaine‐related compounds. Combinations of pretreatments and comparison metrics were assessed using receiver operating characteristic curves to determine the combination with the best discrimination between linked and unlinked populations. Using data from 382 linked and 34, 519 unlinked distances, a classification model was developed using a combination of the standardization and normalization transformations with Canberra distance, resulting in a linked cut‐off with a 0.5% false positive rate. The present study demonstrates the applicability of retrospectively developing a cocaine profiling model using data generated from UHPLC‐TOF‐MS nontargeted drug screening without pre‐existing information about cocaine impurities. The developed workflow was not specific to cocaine and thus could potentially be applied to any seized drug in which there are both sufficient data and impurities present. Abstract : A cocaine profiling method was developed allowing for batch comparison of cocaine seizures based on impurity markers generated from retrospective analysis of nontargeted drug screening data.